REPRODUCTIVE BIOLOGY AND SIZE AT SEXUAL MATURITY OF PENAEUS MERGUIENSIS (DE MAN, 1887) FROM THE SONMIANI BAY LAGOON, BALOCHISTAN, PAKISTAN - N. A. Qureshi; Z. Amanat (Journal of Animal and Plant Sciences, 2014)
The study investigates the vital aspects of reproductive biology: maturation stages of ovaries, spawning season and size at sexual maturity of Penaeus merguiensis. The sampling of Penaeus merguiensis De man, 1887 was conducted from the coastal waters of Pakistan during the period July 2006 to June 2007, from the Damb Bunder, Sonmiani Bay Lagoon locally known as Miani Hor (25° 27' N/ 66° 33' E). Five maturation stages were recognized by the variations in colour as well as development and arrangements of cells. These stages were designated as undeveloped, developing, nearly ripe, ripe and spent. The data show P. merguiensis spawn throughout the year with 2 or 3 peaks being different in different years. The peak spawning activity was observed in NE monsoon and pre monsoon. The results of one way ANOVA showed significant differences for ovarian developmental stages (colouration) and morphological parameters. The size at onset of sexual maturity at when fifty percent of the population was morphologically mature was estimated as (TL50 =15.50 cm), and can be significantly utilized in fisheries management as an indicator for minimum permissible capture size.
Keywords: Reproductive biology; penaeid shrimps; maturation stages; fisheries management; size at maturity